RANCANG BANGUN SISTEM INFORMASI PENDAFTARAN WORKSHOP DAN SYMPOSIUM PADA ORGANISASI JAKNEWS DI JAKARTA - Masria, Masria; Salim, Agus (JURNAL LENTERA ICT, 2020)
In describing and explaining the design of the registration information system for workshops and symposiums at the Jaknews organization in Jakarta. This study uses a descriptive method, which describes and analyzes data based on existing facts and information. The data collection technique used is to conduct a field study which includes observation and literature study. Based on the results of the study, it can be concluded that the Jaknews organization still uses a manual system in carrying out the registration process for workshops and symposiums. This creates several obstacles, namely: participants have to queue because the registration process takes a long time, so it is very time inefficient and slows down performance. Keywords: System, Information, Registration, Workshop, Symposium